P2P Lending Fintech Default: A Comparative Analysis from the Perspective of Islamic Economic Law in Indonesia and Malaysia - Ramadhan, Muhammad Syahri (Sharia Faculty Islamic Economic Law Study Department, 2025)
This paper examines in depth the dynamics of default in the Peer-to-Peer (P2P) Lending fintech industry in Indonesia and Malaysia, with a review from the perspective of Islamic Economic Law. Fintech has become a crucial tool for financial inclusion, but it also increases default risk, especially among young people. The research used is normative legal research with a comparative approach. This study describes how the two countries respond to these challenges through the harmonization of positive law and Sharia principles. Key findings show a glaring regulatory gap between the two countries. In Indonesia, legal protection for the parties remains weak because the DSN-MUI fatwa has not been fully integrated into binding positive law, and there is no efficient dispute-resolution mechanism. The phenomenon often leads to unethical billing practices and privacy violations, which are contrary to the principles of maslahah and muamalah ethics. In contrast, Malaysia features a more mature ecosystem, with strict personal data protection under the Personal Data Protection Act (PDPA) and effective financial dispute mediation institutions. Within the framework of sharia, this study highlights the relevance of the principle of justice as enshrined in QS. Al-Baqarah: 282. The study concludes that to mitigate the impact of defaults and ensure profitability, Indonesia needs to reform its regulations by adopting aspects of Malaysia’s fintech laws, enforcing digital ethics, and providing cheap, fast online dispute resolution to balance rights between creditors and debtors.